Identification of Broad‐Spectrum Dengue/Zika Virus Replication Inhibitors by Functionalization of Quinoline and 2, 6‐Diaminopurine Scaffolds. (1st June 2018) - Kaptein, Suzanne J. F.; Vincetti, Paolo; Crespan, Emmanuele; Rivera, Jorge I. Armijos; Costantino, Gabriele; Maga, Giovanni; Neyts, Johan; Radi, Marco
Abstract: Social and demographic changes across the world over the past 50 years have resulted in significant outbreaks of arboviruses such as dengue virus (DENV) and Zika virus (ZIKV). Despite the increased threat of infection, no approved drugs or fully protective vaccines are available to counteract the spread of DENV and ZIKV. The development of "broad‐spectrum" antivirals (BSAs) that target common components of multiple viruses can be a more effective strategy to limit the rapid emergence of viral pathogens than the classic "one‐bug/one‐drug" approach. Starting from previously identified multitarget DENV inhibitors, herein we report the identification of novel 2, 6‐diaminopurine derivatives that are able to block the replication of both Zika virus and all serotypes of dengue virus (DENV 1–4) in infected cells. Abstract : One (purine) ring to rule them all : Chemistry‐driven exploration of 2, 6‐diaminopurines led us to the discovery of novel broad‐spectrum antivirals (BSAs) that block the replication of both Zika virus and all serotypes of dengue virus (DENV 1–4) in infected cells. These compounds are inexpensive to produce, easy to functionalize, and can be regarded among the few non‐nucleoside broad‐spectrum flavivirus inhibitors reported so far. Our findings may lead to drug candidates for the treatment of flavivirus‐infected and co‐infected individuals.